NILAI PERUSAHAAN DITINJAU DARI PROFITABILITAS, KEPUTUSAN INVESTASI DAN KEPUTUSAN PENDANAAN - Krisdiyanto Krisdiyanto; Gendro Wiyono; Risal Rinofah (Universitas Ahmad Dahlan, 2020)
This research was aimed to analyze of profitability, investment decisions, and funding decisions on firm value. This research belongs to empirical study research. The population in this research is transportation sub-sector which is 43 companies listed on the Indonesia Stock Exchange (IDX). The sample used is to use a purposive sampling method, namely the sampling technique for data sources with certain considerations. Quantitative analysis of the r Square, and hypothesis testing in the form of the F test and t test. The results showed that there was a positive and significant effect on profitability there was also a positive and significant influence on investment decisions, there was also a positive and significant influence on funding decisions, and there is also a positive and significant effect on profitability, investment decisions, and funding decisions on the value of the BEI 2016-2018 transport sub-sector company